LEGISLATION OF THE REPUBLIC OF KAZAKHSTAN IN THE FIELD OF EMPLOYMENT IN THE LIGHT OF SOCIAL MODERNIZATION OF KAZAKHSTAN - Dyussenov Ербол Абаевич; Akhmetov Ерлан Кадиржанович (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2014)
In this article an analysis of policy documents on employment of population and the results of law enforcement practice of the authorized bodies in the field of employment.